The rationale for use of clinically defined outcomes in assessing the impact of pneumococcal conjugate vaccines against pneumonia. (4th March 2021) - Gessner, Bradford D.; Isturiz, Raul; Snow, Vincenza; Grant, Lindsay R.; Theilacker, Christian; Jodar, Luis
ABSTRACT: Introduction : When evaluating the public health value of adult pneumococcal conjugate vaccine (PCV) for pneumonia, regulatory agencies and vaccine technical committees (VTCs) emphasize vaccine serotype (VT), radiologically confirmed community-acquired pneumonia (CAP) to the exclusion of clinically defined pneumonia and thus may underestimate PCV's public health value. Areas covered : We review the critiques that have been raised to using clinically defined pneumonia as a complement to VT-CAP in evaluating the public health value of adult PCVs. Expert opinion : PCV13 efficacies for preventing hospitalized CAP ranged from 6% to 11% and for a combination of primary and secondary care from 4% to 12%, with relatively high associated rate reductions. These efficacy values are larger than estimated from multiplying PCV13 efficacy against vaccine-type CAP by the proportion of CAP identified as vaccine-type through tests, such as a serotype-specific urinary antigen detection assay. Current understanding of pneumococcal epidemiology and limitations of diagnostic tests suggest the efficacy values for clinically defined outcomes are plausible and potentially generalizable. Regulatory agencies and VTCs have accepted clinically defined outcomes for assessing pediatric vaccines and – while additional studies assessing adult clinical CAP VE are needed – they might consider existing data when evaluating adult PCV use.